2021
DOI: 10.48550/arxiv.2106.11959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting Deep Learning Models for Tabular Data

Abstract: The necessity of deep learning for tabular data is still an unanswered question addressed by a large number of research efforts. The recent literature on tabular DL proposes several deep architectures reported to be superior to traditional "shallow" models like Gradient Boosted Decision Trees. However, since existing works often use different benchmarks and tuning protocols, it is unclear if the proposed models universally outperform GBDT. Moreover, the models are often not compared to each other, therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…4.2.1) and transformers-based (Sec. 4.2.2) groups exhibit superior predictive performance compared to plain deep neural networks on various data sets (Gorishniy et al, 2021;Ke et al, 2018Ke et al, , 2019Somepalli et al, 2021). This underlines the importance of special-purpose architectures for tabular data.…”
Section: Summary and Trendsmentioning
confidence: 96%
See 1 more Smart Citation
“…4.2.1) and transformers-based (Sec. 4.2.2) groups exhibit superior predictive performance compared to plain deep neural networks on various data sets (Gorishniy et al, 2021;Ke et al, 2018Ke et al, , 2019Somepalli et al, 2021). This underlines the importance of special-purpose architectures for tabular data.…”
Section: Summary and Trendsmentioning
confidence: 96%
“…We also discuss the key categorical data encoding methods in Section 4.1.1. Gorishniy et al (2021) empirically evaluated a large number of state-of-the-art deep learning approaches for tabular data on a wide range of data sets. Interestingly, the authors demonstrated that a tuned deep neural network model with the ResNet-like architecture (He et al, 2016) shows comparable performance to some state-of-the-art deep learning approaches for tabular data.…”
Section: Related Workmentioning
confidence: 99%
“…After searching reports about his activities during that period, we find that he was racing cars for Porsche, 8 and attending fashion shows as ambassador of Louis Vuitton. 9 Apart from "Wu Yifan", we also observe topics related to "live stream", which is also a new topic that has not been observed in previous analysis. ah ah ah (0.045), like (0.041), thanks (0.035), mom (0.019), new (0.015), teacher (0.014), cry (0.011), shoot (0.010), character (0.009), great (0.008), rush (0.008), baby (0.008), song (0.008), clarify (0.008), donate (0.008), live (0.007), hope (0.007), become (0.007), Beijing (0.007), dry (0.007) 9 cute (0.029), china (0.025), support (0.020), Zhang Zhehan (0.020), child (0.014), apologize (0.013), woman (0.012), nation (0.010), gong jun (0.009), stand (0.008), friend (0.008), engage in (0.008), write (0.008), society (0.007), law (0.007), girl (0.006), chance (0.006), sad (0.006), long (0.005), willing (0.005) 10 Wu Yifan (0.126), Mr (0.048), endorsement (0.028), spokesperson (0.026), road (0.023), expect (0.022), easy Vuitton (0.020), brand (0.019), force (0.016), worldwide (0.016), music (0.014), nice (0.011), cattle (0.009), silly (0.009), high (0.008), congratulations (0.008), Wu (0.007), Li Shubai (0.007), racer (0.006), wish (0.006)…”
Section: Temporal Analysismentioning
confidence: 49%
“…To measure the influence, we construct a decision tree-based model and analyze the feature importance. In a recent study of Gorishniy et al [9], it is found that for heterogeneous data, the baseline performance of GBDT (Gradient Boost Decision Tree) is strictly superior to DNN (Deep Neural Networks). In addition, for decision tree-based models, they are intrinsically more interpretable than deep neural networks.…”
Section: Feature Importance Analysis 51 Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation